INTEGRATING RELIGIOUS VALUES: PAI TEACHER STRATEGY TO IMPROVE STUDENT DISCIPLINE - Wahidiyah, Wahidiyah; Fatmawati, Sri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to reveal and analyze the strategies of Islamic Religious Education (PAI) teachers in integrating religious values to improve student discipline at the Salafiyah Madrasah Aliyah (MA) Pajarakan, Probolinggo. This madrasa plays an important role in forming students' character based on the teachings of Salafiyah Islam. Through a qualitative approach, this research involves observation, interviews and document analysis to understand in depth how PAI teachers use religious values as a basis for achieving the goal of improving discipline. The research method uses descriptive qualitative research, case studies at MA Salafiyah Pajarakan, Probolinggo. The research method used is a qualitative approach with data collection through interviews, observation and in-depth documentation integrating religious values: pai teacher strategies for improving student discipline. The research results show that PAI teachers at MA Salafiyah Pajarakan adopt a holistic and integrated strategy in integrating religious values in daily learning. They not only deliver teaching material, but also act as role models for students. The instillation of religious values is integrated into every aspect of school life, from formal lessons to extracurricular activities. Teachers' activeness in providing guidance, advice and religious approaches also plays a role in shaping students' character and discipline.